Using Guided Meditation for Lowering Senior High School Students’ Anxiety to Speak English as a Foreign Language - Vonia Rahman; An Fauzia Rozani Syafe'i (Journal of English Language Teaching, 2019)
The aim of this paper is to discuss the ways of doing guided meditation for lowering Senior High School students’ anxiety to speak English as a foreign language. Regarding to the writer’s observation supported by other studies find that the students experienced the most anxiety when foreign language speaking activities begin. The noisy atmosphere suddenly changed into silence. The students’ negative perception toward their own ability and other negative evaluation are the main factors why they are too quiet as the teacher asked them to speak English in the classroom. This situation may lead the students’ having bad performance in learning foreign language, meanwhile the demand for having good communication skill in speaking foreign language, especially English is highly significant. Therefore, an English teacher has to encourage the student to speak English by using some useful techniques. One of them is using guided meditation that will benecessary for lowering the level of Senior High School students’ anxiety to speak English as their foreign language.